Living environments of polish seniors - needs and challenges - Domosławska-Żylińska, Katarzyna; Fronk, Marlena; Krysińska, Magdalena; Marczak, Hanna; Partyka, Olga; Kwiatkowska, Katarzyna; Pajewska, Monika; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2018)
Demographic changes in Polish population cause an increase in interest of senior citizens. The environment of living of older people is a particularly important issue. It is important to provide seniors with living space that is a comfortable, safe, adequate to the needs and allows for the longest independent functioning of an elderly person. It is a challenge both for public health and for housing policy.